INVENTORY AND MAPPING OF PROBLEMS IN COMMUNITY RELATED TO HYPERTENSION PREVENTION IN MALANG CITY - Susi Milwatil; Rudi Hamarno; Afnani Toyibah (STIKes Kepanjen, 2023)
Hypertension is the silent killer and can cause death because it increases the risk of developing various diseases such as kidney failure, heart failure, and even stroke. Purpose: to inventory and map health problems in the community related to hypertension prevention in the city of Malang. This type of research is descriptive quantitative survey method. The sampling technique used is accidental sampling. The number of samples is 100 people. Data collection using questionnaires and observation. The research was conducted in Malang City from April to May 2022. The data analysis used was univariate and bivariate data analysis using the chi square test, and the Spearman correlation test. The results showed that the risk factors with the highest proportion were respondents who were aged 45-54 years, had more BMI status, and consumed high-fat foods. The good factor is consuming vegetables and fruits more than 3x a week. Correlation test 1) There is a significant relationship between consumption of vegetables >= 3x a week and blood pressure. 2) There is a significant relationship between the consumption of high-fat foods <3x a week and blood pressure. 3) There is a significant relationship between BMI status and blood pressure. In conclusion, the risk factors for hypertension with the highest proportion are excess BMI and consumption of fatty foods.